SPPL3-dependent downregulation of the synthesis of (neo)lacto-series glycosphingolipid is required for the staining of cell surface CD59 - Kawaguchi, Kohei; Yamamoto-Hino, Miki; Goto, Satoshi (Biochemical and biophysical research communications, 2021)
CD59 is a small glycoprotein modified with a glycophosphatidylinositol (GPI) anchor that prevents the formation of the membrane attack complex, thereby protecting host cells from lysis. A previous study identified that cell surface CD59 staining required the intramembrane protease signal peptide peptidase-like 3 (SPPL3). However, the effect of SPPL3 on the staining of CD59 remains unknown. This study shows that SPPL3 is essential for the surface labeling of CD59 but not of major GPI-anchored proteins. Surface CD59 staining requires the intramembrane protease activity of SPPL3 and SPPL3-mediated suppression of the (neo)lacto-series glycosphingolipids (nsGSLs)—but not N-glycan—synthesis pathway. The abundance of nsGSLs may affect complement-dependent cytotoxicity by altering the abundance or accessibility of cell surface CD59. •SPPL3 is essential for the surface labeling of CD59 but not major GPI-APs.•Intramembrane protease activity of SPPL3 is required for the staining of surface CD59.•SPPL3-mediated suppression of the pathway for N-glycan synthesis is not required for the staining of surface CD59•SPPL3-mediated suppression of the pathway for nsGSL synthesis is required for the staining of surface CD59